Amyand’s hernia- outcome of nylon darn repairs after complicated appendix surgeries in a district hospital: case series - Ali, M.A.; Hagbevor, I.; Kyei, M.Y.; Nanga, S. (My University, 2021)
Introduction: Complicated appendix is a least expected sac content of inguinal hernias that always require appendix surgery and hernia repair. The current recommendations for posterior wall repairs however, continue to attract conflicting views as to which modality gives the best outcome in infected surgical wounds. New posterior wall repair methods with properties to withstand surgical site infections, minimise hernia recurrence, affordable and easy skill to acquire with a potential to be widely adopted are continuosly sort. Aim: To determine the surgical outcomes of complicated Amyand Hernias repaired using the open tissue base Nylon Darn posterior wall re-enforcement method. Method: A retrospective review of medical records of patients who had surgery for emergency inguinal hernia with intra-operative confirmation of complicated appendix in the hernia sac from January 2015 to December 2020 at the Margaret Marquart Catholic Hospital, Kpando were included. Data on age, sex, clinical presentation, surgical procedure, intra-operative findings, post operative complications were captured and presented as descriptive statistics. Results: Twelve out of 286(4.6%) repairs were complicated Amyand Hernias in patients aged 6weeks to 76-years {median age 54.5-years}. Most of them were adults, long-standing hernias. All diagnosis were made on-table. Surgical site infections was the most frequent complication in types III and IV AHs which resolved with antibiotic treatment. Conclusion: The incidence of complicated AHs is higher and should be anticipated in surgeries for long-standing complicated inguinal hernias. Even though complications were significantly associated with longer hospital stay, no second procedure or mortality was recorded.
Research Article
Keywords: Complicated amyand hernia; Complicated appendix; Nylon darn; Surgical site infection; Appendicectomy; Emergency inguinal hernia